Coloniality in the Appropriation of Nature: Agrofuel Production, Dependency, and Constant Primitive Accumulation in the Periphery of Capitalism. (September 2018) - Assis, Wendell Ficher Teixeira; Franco, Sérgio H. Rocha
The expansion of sugarcane monoculture for the production of agrofuels since the early 2000s has caused territorial reconfigurations in the Brazilian countryside. This territorial reordering represents both a lucrative way of employing idle capital and the geographical expansion of capital domains. In the process, new markets are created and leveraged by discourses of environmental conservation while air, soil, and water are depredated and indigenous people, peasants, and quilombolas are dispossessed and dragged into new circuits of accumulation. Linked to the continuous search for new fronts of accumulation and the increasing commodification of nature, Brazilian agrofuel production may be understood as an expression of the logic of coloniality. A expansão da monocultura açucareira com vistas a produção de agro combustíveis tem causado reconfigurações territoriais na área rural brasileira. Implementada desde o princípio dos anos 2000, essa reordenação territorial apresenta ao mesmo tempo o emprego lucrativo do capital ocioso e a expansão geográfica do domínio do capital. Nesse processo, novos mercados são criados e alavancados por discursos ambientalistas, enquanto ar, solo e água são devastados. Demais, a população indígena, os campesinos e os quilombolas sofrem destituição e são forçados a integrar novos circuitos de acumulação. Relacionados à busca de novas frentes de acumulação e à comercialização da natureza, a produção brasileira de agro combustível pode ser compreendida como expressão da lógica da colonialidade.